Endometrioid carcinoma infiltrating atypical leiomyoma: A mimicker of malignant mixed Mullerian tumor - Qury Sabita Mahapatra; Malik Ajay; Sahai Kavita (Wolters Kluwer Medknow Publications, 2014)
Atypical or symplastic leiomyoma is a rare histological variant of leiomyoma. This is a case report of 63-year-old patient who underwent hysterectomy with bilateral salpingo-oophorectomy. Histopathology of the polypoid growth seen in the endometrial cavity revealed atypical leiomyoma infiltrated by endometrioid cancer. Atypical leiomyoma can be misdiagnosed as leiomyosarcoma. Thus, carcinosarcoma was ruled out as it has an ominous prognosis. A diagnosis of atypical leiomyoma infiltrated by endometrioid cancer was given. We report this case as there are very few case reports of the above two pathology occurring simultaneously in the same patient.